Unveiling point defects in titania mesocrystals: a combined EPR and XPS study. (20th August 2018) - Konstantinova, Elizaveta; Minnekhanov, Anton; Beltiukov, Artemii; Ivanov, Vladimir; Sutherland, Andrew J.; Boytsova, Olga
Abstract : Titania mesocrystals, prepared using a polyethylene template, were studied by a combination of electron microscopy, XPS and EPR techniques. Abstract : Titania mesocrystals, prepared using a polyethylene template, were studied by a combination of electron microscopy, XPS and EPR techniques. The electronic structure and local environment of point defects in the TiO2 mesocrystals were deduced from experimental and simulated EPR data. The Ti 3+ /F centers and oxygen defects were shown to be the most photosensitive. The presence of carbon radicals was also demonstrated. Since the point defects govern the photosensitivity and photocatalytic activity of TiO2 in the visible spectral range, the data obtained provide new insights into photocatalytic reaction engineering using titania mesocrystals.